Organoleptic Analysis of Consumer Acceptance of Shredded Mackerel Fish (Scomberomorus sp) - Kaliky, Nurainy (INSTITUT AGAMA ISLAM NEGERI AMBON, 2022)
One of the economically important fish that can be used in the manufacture of shredded fish is mackerel (Scomberomorus sp). This fish is a pelagic fish with white flesh and contains a lot of protein which is one of the elements that are needed in the growth process and increase intelligence in toddlers and children. Making shredded fish is one of the processed diversifications that are very popular with the community and become a favorite food. This study aims to analyze the organoleptic parameters of shredded mackerel (Scomberomorus sp) and to see the extent of consumer preference for shredded mackerel fish. The method used in this study was an experiment using RAL followed by one way anove (SPSS version 23 ibm), using 2 treatments, namely treatment A= Mackerel, and treatment B (steaming temperature): BX = 50ºC-80ºC; BY= 60Cº-95ºC and 3 replications.The results of the study on Anova for the F test at alpha 0.05, it can be seen that the parameters of color, taste and smell do not have a significant effect. Steaming treatment at medium temperature will produce shredded meat that can be accepted by panelists and increase public knowledge about the diversification of processed fishery products Keywords: Fish, Color, Smell, Abon, Scomberomorus sp